Edukasi melalui Media Ular Tangga sebagai Upaya Pencegahan Anemia pada Remaja di Mts Nurul Qur’an Pagutan - Solehah, S.Tr.Gz.,M.Gz, Novia Zuriatun; Dewi, Novianti Tysmala; Lastyana, Wiwin; Rahmiati, Baiq Fitria; Naktiany, Wayan Canny; Jauhari, Thonthowi (ADMA : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2023)
Anemia is associated with mortality and morbidity in adolescents. The prevalence of anemia increases with increasing age. World Health Organization (WHO) data in the Worldwide Prevalence of Anemia shows that there are 1.62 billion people with anemia in the world with the highest prevalence in pre-school age 47.4% and Women of Reproductive Age (WUS) 41.8%. With sufficient knowledge of nutrition, young women will understand the impact of the wrong nutritional behavior that has been applied so far so that efforts to prevent anemia grow if it is marked by changes in knowledge as well as attitudes. This community service activity aims to increase the knowledge of adolescents in preventing anemia. The purpose of counseling for adolescents is so that participants can understand what anemia is, the causes of anemia, prevention of anemia, and examples of food sources of iron. This activity was attended by 50 students grade 1 and 2 and 5 teachers of MTs Nurul Qur’an This activity took place in the MTs Nurul Qur'an Pagutan Hall. The participants were very enthusiastic and active in participating in counseling activities and playing ladders game until the end of the activity. Education using ladders media can affect the level of knowledge of adolescents about balanced nutrition and anemia in adolescents. Teenagers can understand and play an active role in participating in community service activities.